Advances in 3D printed hydroxyapatite-collagen scaffolds in bone regeneration - CHENG Ziyang, HAN Xiaoyan, MAO Keming, LIU Laikui, LIANG Weiwei (Kouqiang yixue)
Bone tissue engineering(BTE)is expected to be used as an autologous bone graft substitute for bone defects, and in the selection of BTE scaffold materials, collagen(Col) and hydroxyapatite(HA) have attracted attention due to their unique biomimetic advantages. Collagen/hydroxyapatite(CHA) composite scaffolds made by combining the two have been shown to have excellent biocompatibility and bone-enhancing potential in various in vitro, in vivo, and clinical studies. With the development of three-dimensional(3D) printing technology in the field of tissue engineering, bone scaffolds constructed using 3D printing methods have been shown to possess superior clinical potential. This review describes new advances in 3D printed CHA composite scaffolds and introduces the application of 3D printed CHA scaffolds in oral and maxillofacial bone regenerative repair.